10.3928/08910162-20100601-03 (CrossRef Listing of Deleted DOIs, 2000)
Background This study examined the relationship between operating room nurses' attitudes toward evidence-based nursing and their practices for preventing surgical site infections. Method This descriptive correlational study was conducted in the operating rooms of two hospitals in Turkey. Of the 150 nurses in the target population, 109 voluntarily participated. Data were collected between January and May 2025 using the Evidence-Based Nursing Attitude Questionnaire and the Nursing Practices for the Prevention of Surgical Site Infection Scale. Results Nurses showed positive attitudes toward evidence-based nursing and high levels of surgical site infection prevention practices. A strong positive association was identified between attitudes and practices (r ≈ 0.80; p < .001). Conclusion Positive attitudes toward evidence-based nursing were strongly associated with higher surgical site infection prevention practices, underscoring the importance of ongoing professional learning in operating room settings.